TRADISI TASAWUF DI PESANTREN: TEORI, EKSISTENSI, KARAKTERISTIK, DAN PERANNYA DALAM KEHIDUPAN KAUM SANTRI - Suji; Ach. Maimun; Moh. Kurdi; Moh Diyaul Murtadho; Abdullah; Fadlillah; Moh. Chalilurrosyid (Jurnal Ikhtibar Nusantara, 2026)
Sufism (tasawuf) is a branch of Islamic scholarship oriented toward spiritual cultivation and purification of the soul. Within the pesantren (Islamic boarding school) tradition, Sufism is not merely taught as academic content but is embodied in daily life through routinized worship, character formation, and pesantren culture. This study aims to analyze the theoretical foundation of pesantren Sufism, its existence within the pesantren educational system, its developing characteristics, and its role in the lives of santri (students). This qualitative-descriptive library research draws on classical Sufi texts, books, and scholarly articles, analyzed through content analysis and source triangulation. The findings show that Sufism in pesantren develops within a Sunni-Sufi orientation grounded in the Qur'an, Hadith, and Ahlussunnah wal Jamaah teachings. Its existence is sustained through the study of classical texts (kitab kuning), routine worship, the exemplary conduct of kiai, and religious practices, while continuously adapting to modernization without losing its doctrinal essence. Sufism further plays a strategic role in shaping santri character, strengthening social solidarity, preserving the Nusantara Islamic tradition, and instilling religious moderation and national responsibility. The study affirms that Sufism remains a relevant foundation for character education amid the dynamics of modern society.